LEGAL DOCUMENTATION AND INFORMATION NETWORK (JDIH) AS AN IMPLEMENTATION OF E-GOVERNMENT SYSTEM IN THE REGIONAL OF REPRESENTATIVE COUNCIL OF THE REPUBLIC OF INDONESIA - Adhiasti, Tryavena Martha; -, Yuwanto - (Journal of Politic and Government Studies, 2025)
This study examines the implementation of the Legal Documentation and Information Network (JDIH) as an e-government initiative within the Regional Representative Council (DPD RI) of Indonesia. The primary objective of this research is to assess the system's role in improving transparency, accountability, and accessibility of legal documentation for stakeholders and the public. By employing qualitative research methods, which include interviews with DPD RI staff and public users as well as document analysis, the study highlights the significant contributions made by JDIH while also addressing its limitations. The findings reveal that the implementation of JDIH has led to remarkable improvements in public access to legal documents. However, challenges such as limited technological infrastructure and low public awareness persist. This research underscores the need for ongoing investment in technology and enhanced public outreach initiatives to fully optimize JDIH’s potential. By providing an in-depth analysis, the study contributes to the broader understanding of how digital governance initiatives function in the context of developing countries